2017
DOI: 10.1364/oe.25.015861
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of magic-wavelength optical dipole trap by using the laser-induced fluorescence spectra of trapped single cesium atoms

Abstract: Based on the multi-level model, we have calculated light shifts for Zeeman states of hyperfine levels of cesium (Cs) 6S ground state and 6P excited state. The magic-wavelength linearly-polarized optical dipole trap (ODT) for Cs 6S |F = 4, m = + 4ñ - 6P |F = 5, m = + 5ñ transition is experimentally constructed and characterized by using the laser-induced fluorescence spectra of trapped single Cs atoms. The magic wavelength is 937.7 nm which produces almost the same light shift for 6S |F = 4, m = + 4ñ ground sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(43 reference statements)
0
8
0
1
Order By: Relevance
“…Compared with the said ways, single atoms have advantages of narrowband, matching atom transition lines and weak coupling of neutral ground-state atoms with background light and external electromagnetic fields. single atom source based on the captured single atom in an optical tweezer [1][2][3] paves the way for quantum repeaters, quantum teleportation, quantum secure communications and linear quantum computing. In 1975, Hansch and Schawlow first put forward the use of the laser to cool neutral atoms [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the said ways, single atoms have advantages of narrowband, matching atom transition lines and weak coupling of neutral ground-state atoms with background light and external electromagnetic fields. single atom source based on the captured single atom in an optical tweezer [1][2][3] paves the way for quantum repeaters, quantum teleportation, quantum secure communications and linear quantum computing. In 1975, Hansch and Schawlow first put forward the use of the laser to cool neutral atoms [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Browaeys group constructed a threedimensional atom array composed of 72 single atoms trapped in optical tweezers, optionally manipulating the spatial position of each atom [8]. In our system, we have already captured [2,9] and transferred [10,11] single atoms to optical tweezer efficiently, built cesium (Cs) magic-wavelength optical dipole trap [2,3], and finally achieved triggered single-photon source at 852 nm based on single atom manipulation [3,12]. * wwjjmm@sxu.edu.cn When manipulating the single atoms in the optical tweezers, it is required that the atoms be captured we must capture all the atoms in the tweezers before finishing all the operations.…”
Section: Introductionmentioning
confidence: 99%
“…[20] and experimentally demonstrated in strong-coupling cavity quantum electrodynamics system [21] for applications in quantum measurement and precision metrology [22]. Previous studies on the magic-wavelength ODT of neutral atoms mainly focus on the transition from ground state to a low-excited state [21][22][23][24][25][26]. In 2005, a blue-detuned magic-wavelength bottle beam trap was proposed for trapping the 5S 1/2 ground state and 50D 5/2 Rydberg state of Rb atoms [27], and recently Barredo et al experimentally demonstrated the bottle beam trap for Rydberg-state Rb atoms [18].…”
Section: Introductionmentioning
confidence: 99%
“…1 for single-photon distributing and storing. The left node is single-cesium (Cs)-atom optical tweezer based 852-nm single-photon source [21][22][23], while the right node is cold or hot Cs atomic ensemble. These two nodes can be connected by ultralow loss 1560-nm telecom singlemode fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Then by employing QFC2, 1560-nm single photons can be converted back to 852-nm single photons, which can interact with the right node via Raman-type memory or the electro-magnetically induced transparency (EIT) -type memory protocols for single- photon storing. We have experimentally achieved 852nm single-photon source based on single-Cs-atom optical tweezer [21][22][23], and we plan to build QFC1 and QFC2 converters for implementation of single-photon distributing and storing protocols.…”
Section: Introductionmentioning
confidence: 99%